Students' Perception towards the Drinking Water Facility at Janapriya Multiple Campus, Pokhara - Tripathi, Krishna Prasad (Janapriya Journal of Interdisciplinary Studies, 2018)
The study entitled "Students' perception towards the drinking water facility at JMC Pokhara" is carried out to find out the perception of drinking water and examine the impact of drinking water on student's health in Janapriya Multiple Campus of Kaski district. The descriptive method was applied to meet the objectives and the survey technique was used to collect necessary information. All the students in JMC(4350) were the population of this study. The sample size was 160 through lottery method. The questionnaire and observation schedule were the major tool of data collection. Campus has its own boring system from 2071/ 0/ 17 B.S. The water was lab tested in the beginning by the microbiology department and recommended that it was safe. Most of the respondents felt that it was needed to test the water time to time and notified to concern people. Nearly 80 percent students said that the water was safe and pure but only eleven students complained. Only 6 students bought it and other 5 brought boiled water from their homes. Thirty one students felt water born diseases during their JMC period but they weren't ensure either from their college water or residential water. Students' perception on water availability in JMC was satisfactory.